EXPLORING ENGLISH EDUCATION MASTER STUDENTS’ METACOGNITIVE AWARENESS IN ACADEMIC WRITING LEARNING ENTERPRISES - Kristian Florensio Wijaya (ELTR Journal, 2022)
Abstract Inculcating a higher degree of metacognitive awareness in the presence of academic writing learning scope is a crucial matter for globalized ELT educationalists since learners can regulate their learning objectives, behavior, motivation, and endeavor for a better purpose. Specifically, this present qualitative study aimed to further investigate English Education Master Students’ metacognitive awareness in academic writing learning enterprises accompanied with the support of 10 narrative written interview inquiries asking about the significance of metacognitive awareness in their academic writing learning activities. Two English Education Master Students batch 2018 and 2020 from Sanata Dharma University were invited to take part in this study. Based on the obtained findings, these two participants concurred that a higher degree of metacognitive awareness gradually transformed them into more persistent and goal-oriented academic writers. In line with those aforementioned findings, it is worthwhile to be recommended for worldwide educators to continually nurture the robust development of graduate EFL learners’ metacognitive awareness to provide more long-lasting holistic academic writing learning values for their future career occurrences. Keywords: Metacognitive awareness, academic writing, narrative inquiry